Ruth Crawford Seeger's worlds innovation and tradition in twentieth-century American music - Allen, Ray ca. 20./21. Jh; Hisama, Ellie M. (Eastman studies in music, 2007)
Interdisciplinary perspectives on the life and work of the esteemed 'ultra-modern' American composer and pioneering folk music activist, Ruth Crawford Seeger (1901-1953)